Responses of LiF Thermoluminescence Dosimeters to Diagnostic 60Co Teletherapy Beams (Bangladesh Journal of Medical Physics, 2017)
Thermoluminescence Dosimeter (TLD) is used as an ionizing radiation detector in the field of clinical radiotherapy, diagnostic radiology, personal radiation monitoring as well as in environmental radiation dosimetry. The sensitivity of all the TLDs is not the same even though the manufacturer produced them in the same batch. The response of TLD at various doses is also not always linear. In the present study fifty-seven rod shaped LiF TLDs had been irradiated by doses of 50cGy, 100cGy, 150cGy and 200cGy using 60Co teletherapy unit of Dhaka Medical College (Alcyon II, CGR, McV, France). The TLDs were placed in the grooves of a slab phantom and then covered by a 0.5cm thick plexiglass sheet. The phantom was then irradiated in the reference condition (10x10cm2 field size, 80cm SSD). After irradiation, readout of TLDs was done using a Harshaw TLD reader (Model 3500). Measurements were performed three times for each dose value and their average was taken. For convenience all fifty-seven TLDs were divided into nineteen groups. Grouping was done according to the response of the TLDs for a fixed dose value. In a particular group of TLDs, variation of the response of the dosimeters is the smallest one. The dose (cGy) response (nC) linearity curve of TLDs for each of the nineteen groups showed to be very close to unity.Bangladesh Journal of Medical Physics Vol.8 No.1 2015 14-21